(untitled) (Research, Society and Development, 2020)
The immune system’s response against SARS-Cov-2 seems crucial to control viral infection, since this system is homeostatic, dynamic and promotes immunoprotection of the organism through the activation of the innate and adaptive immune system via activation of cellular and chemical complexes that recognize, neutralize, metabolize and eliminate heterologous substances, with or without tissue damage. An obesogenic microenvironment can further increase the risk of disease complications, and cause a more virulent viral strain and a more lethal virus. Moreover, physical inactivity as well as poor eating habits impairs the body’s energy metabolism and immune cells due to low-grade chronic inflammation. Studies suggest that light to moderate exercise, as well as mild calorie restriction, as an effective approach to relieve obesity and therefore an interesting strategy to strengthen the immune response during the outbreak of COVID-19, while a vaccine is not developed. Some studies have been shown significant findings in favor of High intensity interval training (HIIT) protocols when compared to moderate intensity exercise, showing how immunological system responds to vigorous to high intensity training. However, HIIT has a lower cost of time, reducing the time/efficiency ratio, that is, a lower cost of time with similar or even better benefits to higher volume exercise programs. Let us not forget: "time is the most precious asset we have".